Synthesis and characterization of citrate-capped gold nanoparticles and their application in selective detection of creatinine (A kidney biomarker) - Akriti Tirkey; Punuri Jayasekhar Babu (Sensors International)
A simple, sensitive, and highly selective detection method was developed for creatinine using citrate-capped gold nanoparticles (C-AuNPs). TEM analysis confirmed the synthesis of the C-AuNPs and they were mostly spherical in shape. FTIR data showed peaks at 3302 cm−1, 1635 cm−1, 1219 cm−1 and 771 cm−1 indicating the presence of O–H, C=C, C–O, C–C groups on the surface of the synthesized C-AuNPs. XRD analysis revealed peaks at 33.8, 44.4, 64.6, 77.5, and 81.6° confirming the crystalline nature of the C-AuNPs. The principle of this method is based on the aggregation of C-AuNPs induced by the creatinine molecules which has been successfully employed for the colorimetric detection of creatinine ranging from 0.3 to 0.8 μg/100 μl (3–8 ppm). The degree of aggregation of C-AuNPs was found to have a linear relationship with the concentration of creatinine which allows the development of a colour gradient based on the varying creatinine concentrations. UV–Vis spectrophotometric analysis further confirmed the selectivity of the method among different analytes such as ascorbic acid, nicotinic acid, polyvinyl pyrrolidone, glucose, uric acid, and bovine serum albumin. It has also been successfully applied for the detection of creatinine in urine mimic samples with good recovery rates. Therefore, this method can be successfully employed for both qualitative and quantitative analysis of creatinine.